Through sand and salt : a tale of discovery across the Sahara - Zunon, Elizabeth (Bloomsbury Children's Books, 2025)
A young boy named Malik accompanies his ábba on a journey on camels across the Sahara to deliver salt, learning its vital role in life and gaining confidence to become a future leader of his caravan.